ROLE OF SOCIAL CAPITAL COMMUNITY BUSINESS DEVELOPMENT PROCESS AGROINDUSTRY PALM SUGAR PROTECTED AREAS IN THE FOREST BUFFER - Tangio, Nurain S. (Universitas Negeri Gorontalo, 2021)
The study aims to determine (1) the state of social capital businesses agro-industry palm sugar in the buffer zones of protected forest sub district of Bulango Ulu Bone Bolango regency, (2) the state of the business development agro-industry of palm sugar in the buffer zones of protected forest sub district of Bulango Ulu Bone Bolango regency, (3) the role of social capital for the development of agro-industrial enterprises palm sugar in the buffer zone of protected forests Bulango Ulu sub district Bone Bolango regency. This research is quantitative. Sources of data in this research are secondary data from the primary data from questionnaires to farmers. The data analysis technique used is descriptive statistics and regression. These results indicate that (1) Social capital is owned by farmers in a fairly good state because it has an average value of 83.32%. This shows that people in a community of palm sugar craftsmen were able to cooperate with each other and mutual cooperation in achieving the common good in a business that was involved. (2) The Palm Sugar Agro-industry business development in the area of protected forest buffer Bulango Ulu sub district Bone Bolango regency has been running quite well because it has an average value of 76.76%. (3) In partial and simultaneously social trust, social norms, social networks and local wisdom a significant effect on the business development process agro-industry of palm sugar in the buffer area of protected forests Bulango Ulu sub district Bone Bolango regency the determinant value of 79.90%.